English language in rural Malaysia: situating global literacies in local practices - Hazita Azman, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
This paper claims that underlying the naturalisation of teaching and learning of English in the Malaysian education system are ideological pressures and political dogmas, often emerging from colonial, urban/rural and even local ethnic conflicts and hierarchies. It suggests therein lie the inherent difficulties of teaching and learning English in rural communities in Malaysia. Three paradigms frame this view in the paper: the overarching view of literacy as a situated and variable social process; the use of an ethnographic perspective in investigating English language and literacy education in Malaysia; the stance on the need for Malaysians to acquire English as an additive rather than as a deficit philosophy.